Prevalence of Vitamin D Deficiency and Associated Factors in Critically Ill Patients: A Multicenter Observational Study - Chen, Kuo-Wei; Chen, Chung-Wei; Yuan, Kuo-Ching; Wang, I-Ting; Hung, Fang-Ming; Wang, An-Yi; Wang, Yin-Chin; Kuo, Yu-Ting; Lin, Yi-Che; Shih, Ming-Chieh; Kung, Yu-Chung; Ruan, Sheng-Yuan; et al. (Frontiers in Nutrition, 2021)
Background: Vitamin D deficiency is common in the general population worldwide, and the prevalence and severity of vitamin D deficiency increase in critically ill patients. The prevalence of vitamin D deficiency in a community-based cohort in Northern Taiwan was 22.4%. This multicenter cohort study investigated the prevalence of vitamin D deficiency and associated factors in critically ill patients in Northern Taiwan. Methods: Critically ill patients were enrolled and divided into five groups according to their length of stay at intensive care units (ICUs) during enrolment as follows: group 1, < 2 days with expected short ICU stay; group 2, <2 days with expected long ICU stay; group 3, 3–7 days; group 4, 8–14 days; and group 5, 15–28 days. Vitamin D deficiency was defined as a serum 25-hydroxyvitamin D (25(OH)D) level < 20 ng/mL, and severe vitamin D deficiency was defined as a 25(OH)D level < 12 ng/mL. The primary analysis was the prevalence of vitamin D deficiency. The exploratory analyses were serial follow-up vitamin D levels in group 2, associated factors for vitamin D deficiency, and the effect of vitamin D deficiency on clinical outcomes in critically ill patients. Results: The prevalence of vitamin D deficiency was 59%, and the prevalence of severe vitamin D deficiency was 18%. The median vitamin D level for all enrolled critically ill patients was 18.3 (13.7–23.9) ng/mL. In group 2, the median vitamin D levels were < 20 ng/mL during the serial follow-up. According to the multivariate analysis, young age, female gender, low albumin level, high parathyroid hormone (PTH) level, and high sequential organ failure assessment (SOFA) score were significantly associated risk factors for vitamin D deficiency. Patients with vitamin D deficiency had longer ventilator use duration and length of ICU stay. However, the 28- and 90-day mortality rate were not associated with vitamin D deficiency. Conclusions: This study demonstrated that the prevalence of vitamin D deficiency is high in critically ill patients. Age, gender, albumin level, PTH level, and SOFA score were significantly associated with vitamin D deficiency in these patients.